Tren Konsumen Generasi Z dalam Pembelian Online Produk Eiger: Implikasi bagi Strategi Pemasaran Bisnis Digital - Hasti Pramesti Kusnara; Raida Sri Rahmawati; Tiara Vindria Rusman Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to analyze Generation Z consumer trends in online purchasing of Eiger products and the implications for digital business marketing strategies. Using quantitative exploratory methods, data was collected through a survey involving 100 Generation Z respondents. Correlation analysis shows that social media use (X1) has a strong positive relationship with online shopping behavior (X2) as well as factors that influence purchasing decisions (X3) . Multiple linear regression tests reveal that social media use significantly influences online shopping behavior, while other factors also have an important role although their influence is weaker. The results of this research indicate that Eiger's digital marketing strategy must prioritize the use of social media to increase interaction and engagement for Generation Z consumers, while also considering various other factors that influence their purchasing decisions.